Evaluation of Implementation of Quality Methodologies in the Engineering Institute of UABC in Mexicali (Indian Journal of Management and Language (IJML), 2024)
This work describes an analysis of the implementation of quality methodologies that generated an improvement in the research, development and teaching activities of the Engineering Institute of Autonomous University of Baja California (EI-AUBC), located in the city of Mexicali. These methodologies are widely used in the industrial sector to prevent accidents, reduce waste, and eliminate rework and to training of workers in any area in the industries. Only that its applications are very little known in the Laboratories of Higher Education Institutions (LHEI) of the Mexican Republic. With this scientific study the results of the investigation activities were more reliability to be take adequate decisions and were made functions with more security taking care of health of researchers and students. The investigation was made in 2019.